Predictors of Cybersex Behavior among College Students in Karawang Indonesia - Nuram Mubina; Wina Lova Riza; Nita Rohayati; Cempaka Putrie Dimala (Edutran, 2023)
The aim of this research is to examine the roles of loneliness, psychological distress, emotional maturity, and self-control as predictors of cybersex behavior among college students in Karawang, Indonesia. The research method used in this research is an associative quantitative approach with the convenience sampling technique, which selects 349 college students in Karawang who meet the research characteristics as respondents. The data collection in this research was conducted using five Likert-scale models, which are self-control, loneliness, psychological distress, emotional maturity, and cybersex behavior scales. The data analysis in this research utilizes the hypothesis testing of multiple linear regression analysis. Based on the data analysis results, it is indicated that each predictor partially plays a role in cybersex behavior. Furthermore, loneliness, psychological distress, emotional maturity, and self-control collectively also play a role as predictors of cybersex behavior among college students in Karawang, Indonesia, with an influence of 16.8%.